Voices for inclusive and sustainable growth Lao PDR country partnership strategy civil society stakeholder consultation. - Mercer Blackman, Valerie (Asian Development Bank, 2017)
As part of the preparation of the proposed country partnership strategy 20172021 for the Lao PDR, ADB organized stakeholder consultations with civil society in May 2016.